Atividade lipolítica, proteolítica e resistotipagem de cepas de staphylococcus aureus - Rodrigues, Jessica Bezerra dos Santos (2013)
Staphylococcus aureus is widespread in nature and is the bacteria most often found in skin infections, although it is able to colonize many organ in the human body. This pathogen can also to contaminate food and staphylococcal food poisoning is one of foodborne diseases more common around the world. This study aimed to isolate and characterize samples of S. aureus isolates from surface preparation of meat and vegetables in public hospitals located in the city of João Pessoa - Paraíba - Brazil, as the production of lipase, protease, antibiotic resistance profile and detection of mecA. Further, evaluation was made in the production of lipase strains of S. aureus isolated from animals (udder and nasal cavities), food (cottage cheese) and infected human wounds (hospital). It was observed lipase production in isolates from human wounds (43/50) animals (16/30), cheese (34/41), bench preparation of meat (24/24) and surface preparation plant (22 / 24). All isolates surface preparation of meat, vegetables and cheese produced protease precipitation with zones of diameters ranging from <0.5 to 4 mm. Among the 48 S. aureus isolates from food processing surfaces tested, 100% were sensitive to chloramphenicol, norfloxacin and methicillin. Twelve isolates were resistant to erythromycin and tetracycline, whereas all isolates were resistant to penicillin and streptomycin. The fragment corresponding t the mecA gene was not identified among isolates. The lipolytic and proteolytic activities, as well as antibiotic resistance (even those already with no therapeutic value) constitute important epidemiological and genetic markers may contribute to the characterization of samples environment or host-specific, and, if performed periodically to distinguish those new strains endemic.